Protocol for ‘Resilient Caregivers’: a randomised trial of a resilience-based intervention for psychologically distressed partner caregivers of patients with cancer - Susanne Oksbjerg Dalton; Peter Genter; Beverley Lim Høeg; Camilla Jensen Hamre; Elisabeth Anne Wreford Andersen; Bjørn Ribers; Pernille Envold Bidstrup (BMJ Open, 2021)
Introduction Intimate partners of patients with cancer often experience significant distress, but there is a lack of psychological interventions that specifically target this population. ‘Resilient Caregivers’ is a novel resilience-based intervention for distressed partner cancer caregivers. The intervention was developed according to a resilience framework focusing on meta-reflective skills, coping strategies and value clarification. The aim of this study is to evaluate the effectiveness of this intervention in a randomised trial.Methods and analysis Eighty participants will be invited through the Oncology Department at Herlev Hospital, Denmark and randomised to either the intervention or usual care. Participants are eligible if they are partners (married or unmarried) of patients diagnosed with cancer and experience distress (>4 on the distress thermometer). ‘Resilient Caregivers’ consists of seven manualised group sessions (2.5 hours each), focusing on resilience in relation to being a partner caregiver of a patient with cancer. The primary outcome is symptoms of anxiety, while secondary outcomes include distress, depression, quality of life, sleep quality and resilience. Data will be collected at baseline, 3, 6 and 12 months follow-up using validated scales, and analysed using mixed models for repeated measures.Ethics and dissemination This study will follow the ethical principles in the Declaration of Helsinki and has been reviewed by the Ethics Committee of the Capital Region of Denmark (Journal no. 18055373). Written informed consent will be obtained from all participants. Results will be reported through scientific peer-reviewed journals and relevant conferences.Trial registration number NCT04610034.